Differences in physical activity and nutritionand silhouette-related behaviours in male and female students in selected European countries - Bergier, Barbara; Bergier, Józef; Niźnikowska, Ewelina; Junger, Ján; Salonna, Ferdinand; Ács, Pongrác; Frömel, Karel (Annals of agricultural and environmental medicine, 2018)
INTRODUCTION: As indicated by the WHO, lifestyle plays a unique role in human health, which in turn is determined to a great extent by physical activity and nutrition. It must be borne in mind that physical activity should be systematic and regulated by an age-appropriate exercise intensity. All this indicates that learning about students' lifestyle, with a particular focus on physical activity is vital as it these young people who aspire to the role of the future elites. OBJECTIVE: The aim of the study is to evaluate the level of physical activity, nutrition- and silhouette-related behaviours of male and female students to assess the relationships between these variables in students from the Visegrad Group countries. MATERIAL AND METHODS: The study was conducted in 2015 and involved 2,497 students attending three undergraduate levels aged - x - 21,76, (SD-1,80) - 1,211 males (48.5%) and 1,286 females (51.5%). The IPAQ long-form and a questionnaire by the Polish Chief Sanitary Inspector were used. RESULTS: Physical activity was significantly higher in male than female students. An important relationship was observed among the larger number of consumed meals, level of physical activity, and silhouette-related behaviours in male students, which was not the case with females. However, there was an important correlation between physical activity in males and females who exercised to increase or decrease body weight (musculature), and took medications to increase body weight (musculature). CONCLUSIONS: Both males and females showed pro-health attitudes related to the level of physical activity and nutrition- and silhouette-related behaviours.
Keywords: Surveys and Questionnaires; nutriční stav; Humans; students; univerzity; studenti; Female; Attitude to Health; postoj ke zdraví; mladý dospělý; zdravé chování; lidé; Universities; Europe; Nutritional Status; průzkumy a dotazníky; ženské pohlaví; Male; Adolescent; physical activity; nutrition-related behaviours; IPAQ-L; Young Adult; Body Weight; Exercise; Students; tělesná hmotnost; mužské pohlaví; cvičení; silhouette-related concerns; Evropa; mladiství; Health Behavior